Number of keratinocytes and melanocytes in cell suspensions obtained from partial-thickness epidermal cuts and suction blister roofs for vitiligo treatment: a prospective randomized comparative study - Tag S Anbar; Tarek S El-Ammawi; Sahar S Mohammed; Amal T Abdel-Rahman (Wolters Kluwer Medknow Publications, 2020)
Background Treatment of vitiligo not responding to conventional therapies involves the replacement of the absent melanocytes by surgical maneuvers, including minigrafting and cultured and noncultured cell suspension grafting. Cell suspensions were prepared from epidermal cuts or suction blister roofs. Success of these grafts depends on the transplanted cells. Objective The aim was to compare the number of melanocytes and keratinocytes in suspensions prepared from suction blister roofs vs that of epidermal cuts obtained by Thiersch knife. Patients and methods The study was carried out on twenty patients with nonsegmental vitiligo attending the outpatient clinic of El-Minia University Hospital. They were randomly divided into two groups to be treated by autologous noncultured cellular grafting. One group was treated using cellular suspensions prepared from epidermal cuts and the other obtained by suction blister roofs. The mean number of keratinocytes and melanocytes was estimated using certain equations, and the presence of melanocytes was confirmed by special stains. Results Despite that the number of melanocytes was slightly less in group 2 compared with group 1, there was no statistically significant difference between total epidermal cells or melanocytes' numbers of both groups (P>0.05). Conclusion This is the first report to compare the number of epidermal cells and melanocytes in the suspensions obtained from partial-thickness epidermal cuts and suction blister roofs as a source of noncultured cell suspension for the treatment of vitiligo. Both groups were comparable in the melanocytes' numbers, so both sources could be used for noncultured cellular grafting in vitiligo.